2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7320112
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological correlates in Mild Cognitive Impairment detected using group Independent Component Analysis

Abstract: Alzheimer's disease is the most prevalent cause of dementia. Mild Cognitive Impairment (MCI) is defined as a grey area between intact cognitive functioning and clinical dementia. Electroencephalography (EEG) has been used to identify biomarkers in dementia. Currently, there is a great interest in translating the study from raw signals to signal generators, trying to keep the relationship with neurophysiology. In the current study, EEG recordings during an encoding task were acquired in MCI subjects and healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The use of independent component analysis (ICA) in EEG has evolved from a technique oriented to help in artifact detection and correction [76,77], to identify neural process and biomarkers [27,33,78,79]. Using recordings obtained at rest in 144 subjects, Congedo et al [80] reported seven sources distributed across the cortex, where three of them were also related to the Precuneus, that would serve to assessment and diagnosis of abnormal brain functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of independent component analysis (ICA) in EEG has evolved from a technique oriented to help in artifact detection and correction [76,77], to identify neural process and biomarkers [27,33,78,79]. Using recordings obtained at rest in 144 subjects, Congedo et al [80] reported seven sources distributed across the cortex, where three of them were also related to the Precuneus, that would serve to assessment and diagnosis of abnormal brain functioning.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis was based in gICA, to extract the neuronal sources related to resting state, and inverse solution methods to locate the neuronal sources in the brain cortex. The concatenation of subject data for gICA analysis has been applied to study Mild Cognitive Impairment [33], Alzheimer disease [34] and Attention-Deficit Hyperactivity Disorder [35].…”
Section: Introductionmentioning
confidence: 99%
“…The same author, in a subsequent work, discussed how the gICA approach gives replicable physiological components that could help in diagnosis and assessment of abnormal brain functioning (Congedo, John, Ridder, & Prichep, 2010). The concatena-tion of subject data for gICA analysis has been applied to the study of Mild Cognitive Impairment (Ochoa et al, 2015), Alzheimer’s disease (Zervakis, Michalopoulos, Ior-danidou, & Sakkalis, 2011) and Attention-Deficit Hyperactivity Disorder (Ponomarev, Mueller, Candrian, Grin-Yatsenko, & Kropotov, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The same author, in a subsequent work, discussed how the gICA approach gives replicable physiological components that could help in diagnosis and assessment of abnormal brain functioning . The concatenation of subject data for gICA analysis has been applied to the study of Mild Cognitive Impairment (Ochoa et al, 2015), Alzheimer's disease (Zervakis, Michalopoulos, Iordanidou, & Sakkalis, 2011) and Attention-Deficit Hyperactivity Disorder (Ponomarev, Mueller, Candrian, Grin-Yatsenko, & Kropotov, 2014).…”
Section: Introductionmentioning
confidence: 99%